The Influence of Organizational Culture, Training and Communication toward Employee Performance in PT Multi Jaya Samudera - Yusuf Ronny Edward; Calen (Budapest International Research and Critics University, 2020)
This study aims to determine the effect of organizational culture, training and communication on employee performance at PT Multi Jaya Samudera. This research was conducted at PT Multi Jaya Samudera which lasted for 4 (four) months, starting from November 2019 to February 2020. This study uses a quantitative associative method with structural equation modeling (SEM) analysis tools. The sampling technique used is the census sampling. The respondents of this study were all employees of PT. Multi Jaya Samudera as many as 95 people. The instrument used was a questionnaire to collect data from organizational culture, training, communication and employee performance variables. Descriptive analysis results for organizational culture variables, training, communication and employee performance at PT. Multi Jaya Samudera is in the good category. Based on SEM analysis, organizational culture, training and communication have a positive and significant influence on the performance of the employees of PT. Multi Jaya Samudera. The contribution of organizational culture, training and communication variables explained the employee performance variable by 0.749 or 74.9%. The remaining 0.251 or 25.1% is influenced by other independent variables not examined in this study.